TOURIST SHIPS ON THE DANUBE AS AN OPPORTUNITY FOR EXPORT OF MEAT AND MEAT PRODUCTS - Tešanović, Dragan; Vuksanović, Nikola; Kalenjuk, Bojana; Portić, Milijanko (Economics of Agriculture, 2015)
Tourism development launches growth of other complementary industries. River tourism, as a special selective tourism form, experiences intensive development, with an importance for all the regions through which the Danube, as an integral part of the Rhine - Main – Danube waterway, flows. During cruising, the largest consumption is achieved on the ship itself, where meat and meat products are an integral element of every meal and represent the most expensive component of the dish. The task of this paper is to analyse the consumption of meat and meat products on six tourist ships run by to "Grand Circle Corporation" in 2013, in order to point out the possibility of supplying them with meat and meat products from sources in the territory where the ships sail. The paper presents the current suppliers and manufacturers of meat and meat products in Republic of Serbia that could supply the company "Grand Circle Cruise Line" and other tourist ships that cruise on the Danube. Also, the research indicates that the export of meat products from the Republic Serbia could have a signifcant effect on improving the agricultural conditions and food production through increased competition, assuming the Serbian manufacturers supply most of tourist ships and not only the six ships analysed in this paper. Research results, specifcally, point out the possibility of increasing export of poultry and beef if the potential demand of each of the eight companies with their 54 ships which operate tourist cruises on the Danube is taken into account. The data have been systematized, analysed and presented statistically in tables and graphs.